Associação entre prematuridade, hábito de sucção de chupeta e tipos de aleitamento infantil - Larissa Carcavalli Santos (2016)
Preterm infants might experience more difficult in breastfeeding and therefore are more vulnerable to the use of pacifiers and/or bottles in their life. This research aimed to evaluate the association between prematurity, pacifier sucking habit and types of infant feeding in children aged 3 to 5 years old attended at the University Hospital Clinic and two preschools in the city of Belo Horizonte, Brazil. Two hundred and fifty children took part in this retrospective cross-sectional epidemiological study with control group. The sample was divided intro two groups: the case group was formed by preterm infants attended at ACRIAR project (Risk Child Clinic, Clinic Hospital of the Federal University of Minas Gerais- UFMG) and the control group were preschool children enrolled at a public school and a private school, chosen by convenience who were full term infants. A pre-tested questionnaire was used for collecting data of full term children. Parents answered a structured questionnaire related to prematurity, infant feeding methods, pacifier sucking habits and demographic aspects. Parents or responsible received the questionnaire attached to the childrens homework. They answered it at home and sent it back to the school. Collection of data of the preterm children was based on the clinical records of ACRIAR project. The same questionnaires of questions were adopted for both groups: preterm and full term children. Data were entered the Statistical Package for the Social Sciences Software (SPSS) version 21.0 for statistical analysis. Chi-square test was used to test the association between the dependent variable (gestational age at birth: preterm or full term children) and the independent variables. Prevalence ratio values were estimated for each independent variable by using multiple Poisson regression. Variables with p <0.05 in the bivariate Poisson regression analysis were included in the multivariate analysis. The Research Ethics Committee of UFMG approved the research (protocol # 49803115400005149). Most of the children were female (n=137; 54.8%), aged 5 years old (n=117; 46.8%) and belonged to families with monthly income higher than 2 minimum wages (n=121; 48.4%). Mothers of preterm children were younger and the majority had less than 30 years old (n=44; 67.7%); while mothers of full term children were older than 30 years old (n=104; 78.2%). The final multiple Poisson regression model showed that monthly income lower than two minimum wages (PR = 2.068; 95% CI = 1.418-2.016), the use of pacifier (PR = 1.730; 95% CI = 1.100-2.721) and breastfeeding for less than 6 months (PR = 1.010; 95% CI = 1.302-2.829) were more prevalent among preterm infants. The use of pacifiers, the shorter breastfeeding duration and low family income were factors associated with prematurity in children.